Movement of transposable elements contributes to cichlid diversity. Issue 24 (13th November 2020) - Carleton, Karen L.; Conte, Matthew A.; Malinsky, Milan; Nandamuri, Sri Pratima; Sandkam, Benjamin A.; Meier, Joana I.; Mwaiko, Salome; Seehausen, Ole; Kocher, Thomas D.
Abstract: African cichlid fishes are a prime model for studying speciation mechanisms. Despite the development of extensive genomic resources, it has been difficult to determine which sources of genetic variation are responsible for cichlid phenotypic variation. One of their most variable phenotypes is visual sensitivity, with some of the largest spectral shifts among vertebrates. These shifts arise primarily from differential expression of seven cone opsin genes. By mapping expression quantitative trait loci (eQTL) in intergeneric crosses of Lake Malawi cichlids, we previously identified four causative genetic variants that correspond to indels in the promoters of either key transcription factors or an opsin gene. In this comprehensive study, we show that these indels are the result of the movement of transposable elements (TEs) that correlate with opsin expression variation across the Malawi flock. In tracking the evolutionary history of these particular indels, we found they are endemic to Lake Malawi, suggesting that these TEs are recently active and are segregating within the Malawi cichlid lineage. However, an independent indel has arisen at a similar genomic location in one locus outside of the Malawi flock. The convergence in TE movement suggests these loci are primed for TE insertion and subsequent deletions. Increased TE mobility may be associated with interspecific hybridization, which disrupts mechanisms of TE suppression. This might provide a link between cichlid hybridization and accelerated regulatory variation. Overall, our study suggests that TEs may be an important driver of key regulatory changes, facilitating rapid phenotypic change and possibly speciation in African cichlids.